Pattern and trend of non-odontogenic orofacial pain at a tertiary health facility in Sub Saharan West Africa - Gbadebo, Olaide; Kolude, Bamidele (Journal of Stomatology, 2015)
Introduction. The study aimed at determining the incidence and trend of non-odontogenic orofacial pain at a tertiary health facility in Sub Saharan West Africa. Material and method. A 28-year retrospective analysis of records of non-odontogenic orofacial pain conditions at the Dental Centre, University College Hospital Ibadan. All new cases diagnosed based on medical history and adequate radiographic and clinical examination at the clinic during the study period were included. Result. A total of 658 new cases of non-odontogenic lesions consisting of: 41.2% infective conditions, 24.5% neoplasms, 13.25% stress disorders/aphthous ulcers, 9.4% neural disorders, 9.1% temporomandibular pain disorders and 2.6% immunological disorders were reviewed. There was a significant change in the trend of more infective conditions at the earlier stages to non-infective conditions with neoplastic lesions predominating at the later stages (p=0.00). There was also an upward increase in all non-infective orofacial pain conditions except stress-related lesions over the study period. Conclusion. Non-odontogenic orofacial pain was observed to be relatively rare at our study centre. However, there is progressive increase in non- infective conditions especially cancer-related, which is consistent with general global trend. There is a need for definitive approach to address this emerging public health problem of orofacial cancer and other non- infective types of orofacial pain conditions at the study centre and dependent community.